Integrating Universal Behavioral Screening Within Program-Wide Positive Behavioral Interventions and Supports. (January 2016) - Burke, Mack D.; Rispoli, Mandy; Clemens, Nathan H.; Lee, Yuan-Hsuan; Sanchez, Lisa; Hatton, Heather
Universal behavioral screening is a major part of positive behavioral support and response to intervention systems. Program-wide positive behavioral interventions and supports (PBIS) focuses on establishing social, emotional, and behavioral competence through promotion of a small set of behavioral expectations that are agreed upon, taught, and reinforced by all teachers across all settings. This study explored the validity of a novel approach to universal screening in program-wide PBIS whereby a "brief" screening tool for determining behavioral risk was developed using child adherence to program-wide behavioral expectations. Sixty-five children in a Head Start center were screened using an expectation-based screening procedure developed from the program-wide expectations. Two standardized emotional and behavioral rating scales were then administered as criterions. Results revealed convergent associations between the extent of children's adherence to program-wide expectations and the standardized criterion instruments in risk areas associated with hyperactivity, conduct, and externalizing problems. Classification accuracy analyses provided preliminary support for predicting several domains of behavioral risk.